2015
DOI: 10.1002/ep.12099
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing furfural concentration from wheat straw and Eucalyptus globulus by nonisothermal autohydrolysis

Abstract: The autohydrolysis process as a method for selective extraction of hemicelluloses and conversion to furfural was proposed for lignocellulosic raw materials. Samples of wheat straw (WS) and Eucalyptus globulus (EG) were subjected to nonisothermal autohydrolysis, defined by temperature 180–240°C. Within a biorefinery scheme for the selected materials, the aim of this study is both (a) to optimize furfural processing technology to enable higher yields and improved productivity from EG and WS by autohydrolysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…The relative proportions of the various saccharides depend on the severity of the operational conditions. Pentoses and higher saccharides made up of pentoses can be converted to furfural (F) by hydrolysis/dehydration reactions (Sánchez et al 2013;Nakagame et al 2014;Baktash et al 2015;García-Domínguez et al 2015;Koch and Kindler 2015;Liu et al 2015). F, a commercial product with a favourable market forecast (Dalin Yebo 2015), was considered as one of the top 12 platform chemicals derived from biomass in a report from the U.S. Department of Energy (Werpy et al 2004), which was updated 6 years later (Bozell and Petersen, 2010;De Jong et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The relative proportions of the various saccharides depend on the severity of the operational conditions. Pentoses and higher saccharides made up of pentoses can be converted to furfural (F) by hydrolysis/dehydration reactions (Sánchez et al 2013;Nakagame et al 2014;Baktash et al 2015;García-Domínguez et al 2015;Koch and Kindler 2015;Liu et al 2015). F, a commercial product with a favourable market forecast (Dalin Yebo 2015), was considered as one of the top 12 platform chemicals derived from biomass in a report from the U.S. Department of Energy (Werpy et al 2004), which was updated 6 years later (Bozell and Petersen, 2010;De Jong et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the deactivation of solid acid is still a problem needed to be solved. Garc ıa-Dom ınguez et al [21] have used the autohydrolysis process to optimize furfural process technology and obtained high furfural yield. Lewis acid involving most of metal chlorides could improve furfural yield by accelerating reaction rate with the help of metal cations and chloride ions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was observed that the glucan initially present in the raw material remained unchanged to a large degree (>80%) and that the polysaccharides of the hemicellulosic fraction of the original raw material were basically solubilized (the xylan, araban, and acetyl groups). Between 65% and 82% of the hemicelluloses present in the raw material was recovered in the liquid phase [49].…”
Section: Resultsmentioning
confidence: 99%